Show me a sign - LeZotte, Ann Clare (Scholastic Press, 2020)
Mary Lambert has felt safe and accepted on her beloved island of Martha's Vineyard, comforted by the fact that her great-great-grandfather was the first deaf islander and paved the way for many to learn sign language. However, when Mary's brother dies and her family shatters amidst land disputes with the English settlers and Wampanoag people, it paves the way for an opportunistic young scientist to come and study the island's prevalent deafness, and, without moral scruples, he begins using Mary as a "live specimen" for increasingly cruel experiments.